The Relationship between CD27 Negative and Positive B Cell Populations in Human Peripheral Blood - Wu, Yu-Chang Bryan; Kipling, David; Dunn-Walters, Deborah K. (Frontiers in Immunology, 2011)
CD27 expression has been used to distinguish between memory and naive B cells in humans. However, low levels of mutated and isotype-switched CD27-IgD- cells are seen in healthy adults, and these are increased in some autoimmune diseases and in the elderly. Thus CD27 is not a universal marker of memory B cells in humans. Various hypotheses have been put forward as to the function of the CD27- memory population. Since we have previously found high throughput IGHV repertoire analysis useful to distinguish “innate-like” memory B cells (CD27+IgD+), we have employed similar analyses to elucidate the relationship between CD27- and CD27+ memory B cells. IgM+IgD- memory cells in both the CD27+ and CD27- compartments share the unique characteristics of the “innate-like” IgM+IgD+CD27+ cells. The switched CD27+ and CD27- memory cells share a similar IGHV repertoire, having more in common with each other than with “innate-like” memory cells, although it is interesting that IgG2 and IgA2 subclasses of antibody in both switched memory populations have a more “innate-like” repertoire. Clonality analysis shows evidence of a close clonal relationship between the two populations in that both CD27- and CD27+ switched memory cells can be found in the same genealogical tree. The expression of CD27 does not appear to occur in a linear developmental fashion, since we see CD27- cells as precursors of CD27+ cells and vice versa. Despite the similarities, the CDR-H3 repertoire of the CD27- cells is significantly different from both the CD27+IgD+ and CD27+IgD- populations, indicating that perhaps the lack of CD27 might be related to binding properties of the Ig CDR-H3 region.